Exploring the impact of profitability, debt covenant, and financial flexibility on firm value: Does company growth moderate the relationship? - Evianti, Dessy; Hasanudin, Agus Ismaya; Mulyasari, Windu; Soleha, Nurhayati (Edelweiss Applied Science and Technology, 2025)
This study examines the impact of profitability, debt covenants, and financial flexibility on firm value, with a specific focus on the moderating role of company growth. Using panel data regression analysis, this research analyzes financial data from ten of the largest state-owned enterprises (SOEs) in Indonesia from 2019 to 2024. The findings reveal that profitability positively influences firm value (β1=0.184, p<0.01), while debt covenants exert a negative impact (β2=−0.145, p<0.05), suggesting that excessive financial constraints limit corporate growth potential. Additionally, financial flexibility enhances firm value (β3=0.201, p<0.01), highlighting the importance of liquidity reserves in maintaining market confidence. Furthermore, company growth (β4=0.172, p<0.05) has a direct positive effect on firm value, indicating that firms with higher growth rates tend to be valued more favorably. The study also finds that company growth moderates these relationships. Specifically, higher growth strengthens the positive effect of profitability on firm value (β5=0.064, p<0.05), while it amplifies the negative impact of debt covenants (β6=−0.087, p<0.05). Financial flexibility plays a crucial role in high-growth firms (β7=0.103, p<0.01), enabling them to seize expansion opportunities while mitigating financial distress risks. These results provide valuable insights for policymakers, corporate managers, and investors, emphasizing the need for optimal debt management, enhanced profitability strategies, and financial flexibility in driving firm value. Future research should incorporate broader industry comparisons and macroeconomic variables to further refine these findings.